Comparison of 3-D Integration Schemes for Enriched Elements in XFEM (2016)
The XFEM is a technique developed for the numerical simulation of fracture mechanics problems. The method shows several advantages. But some questions arise that should be handled with some care. Numerical integration of the enriched elements is one of these issues. In this work we have compared two avalaible techniques for its integration. One is a classic integration scheme and another is a scheme specifically developed for this kind of elements. The differences on the results are minimal, but not in their implementation difficulty. Hence, the classical integration is recommended.